An interactive, interoperable and ubiquitous mixed reality application for a smart learning experience. (2018) - Longo, Francesco; Nicoletti, Letizia; Padovano, Antonio
This article presents an innovative comprehensive platform that includes an interactive, interoperable and ubiquitous mixed reality application that will bring beyond the way cultural digital resources are created, disseminated, preserved and re-used. As part of an extensive research effort carried out by the authors to foster the utilisation of the most recent technologies in the field of cultural heritage, this article goes further in the design and development of a prototype of an intelligent, interactive and interoperable comprehensive platform for the 21st century museums (I3-CPM). Since I3-CPM explores unconventional ways to deliver cultural contents (virtual and augmented reality, serious games, holography, simulation, knowledge based systems, vocal interaction technologies, etc.), it is expected to provide users with a new and smart learning experience. The OUTSIDE-REAL application is here described as part of the I3-CPM framework: it provides intuitive navigation of mixed reality cultural contents and storytelling through an intelligent knowledge navigator and vocal assistant, called SOPHOS, thus offering the visitors a user-driven, interactive and meaningful learning experience at the cultural heritage site.